Molecular Characteristics of H6N6 Influenza Virus Isolated from Pigeons in Guangxi, Southern China - Li, Meng (Genome Announc, 2015)
Here, we report the complete genome sequence of an H6N6 avian influenza virus (AIV) isolated from a pigeon in Guangxi, southern China, in 2014. The eight RNA segment genes shared a high nucleotide identity (97 to 99%) with H6N6 subtypes of AIV isolated from ducks in the regions around Guangxi Province. The finding of this study will help us understand the ecology and molecular characteristics of H6 avian influenza virus in wild birds in southern China.